Training on e-commerce marketing of ornamental plants for the women farmers group in Petiga Village, Tabanan Regency - Ni Made Ayu Natih Widhiarini; Kadek Ayu Ekasani; I Wayan Eka Mahendra; Ni Luh Putu Daniella Santika Dewi; Putu Haskara Wijana; Adis Audiana Syafri (Universitas Muhammadiyah Magelang, 2023)
One of the centers for ornamental plants in Bali is located in Petiga Village. However, the marketing of ornamental plants in Petiga Village has not yet embraced digital methods, limiting its reach primarily to the local market. The objective of this community service project is to introduce and train groups of women farmers in utilizing e-commerce to expand the marketing of ornamental plants. This community service activity comprises three main stages: preparation, implementation, and evaluation. The results obtained reveal that the women farmers' group has gained knowledge about marketing ornamental plants through e-commerce. Based on this, it can be concluded that the socialization and training on marketing ornamental plants through e-commerce have provided farmer groups with a better understanding of using digital media. As a next step, farmers still require additional skills in using social media platforms as digital marketing tools, such as Facebook, Instagram, TikTok, and others.